Integrated control of neglected zoonotic diseases in Africa: Applying the “One Health” concept - World Health Organization (World Health Organization, 2009)
Control of neglected zoonotic diseases (NZDs), by simultaneously saving lives and securing livelihoods, offers an important opportunity for alleviating poverty in remote rural areas and among marginalized periurban communities of poor livestock keepers in Africa and other less developed areas of the world. The meeting held at the headquarters of the International Livestock Research Institute (ILRI) in Nairobi, Kenya during 13–15 November 2007 was supported jointly by the World Health Organization (WHO), the European Commission (EU), ILRI, the DBL-Centre for Health Research and Development (DBL), the Food and Agriculture Organization of the United Nations (FAO), the World Organisation for Animal Health (OIE) and the African Union (AU). It focused on the need to and opportunities for combating NZDs in Africa as the most affected continent where all of the NZDs occur; and where their burden on society hinders development and has a serious impact on health and agriculture. The objective of the meeting was to formulate a strategic framework for implementing the action points for combating NZDs that arose from an initial meeting held at WHO in 2005. These actions were to promote a “one health” integrated approach to control of NZDs, to develop plans for advocacy and information, to improve diagnosis and surveillance, to foster research, to build capacity and to strengthen prevention and control activities. A multidisciplinary group of researchers, programme managers and policy-makers from across the African continent was brought together with international experts and representatives of regional and international technical support agencies and organizations to address practical, institutional, political and resource-related issues associated with integrated surveillance, prevention and control of NZDs in Africa.